Effect of Dual Space Inquiry E-Student Worksheet on Improving Physics Learning Outcomes in Temperature and Heat Material - Zelfi Nurfadillah; Fuja Novitra; Hufri Hufri; Hayyu Yumna (Universitas Negeri Padang in collaboration with Association of Mathematics and Natural Sciences Institution for Education of Teaching Staff Indonesia (AMLI), 2026)
Low student learning outcomes on the topics of temperature and heat indicate the need for learning materials that can increase student engagement in the learning process. Ideally, physics learning can facilitate students to actively construct knowledge through inquiry activities supported by the use of technology. One solution that can be applied is Dual Space Inquiry E-Student Worksheet, which integrates online and offline learning activities. This study aims to find out the effect of using Dual Space Inquiry E-Student Worksheet on the physics learning outcomes of 11th-grade students at SMA Negeri 1 Pancung Soal for the 2025/2026 academic year. This study used a quasi-experimental method with a posttest-only control group design. The research population consisted of 207 students, with classes XI F1 and XI F2 purposively selected as the sample. Learning outcome data were collected through objective tests and analyzed using a t-test. The analysis results showed a significance value of 0.047 < 0.05, so H₁ is accepted. The study’s findings indicate that using a Dual Space Inquiry E-Student Worksheet has a significant effect on students’ learning outcomes. These results suggest that integrating online and offline learning spaces can create a more meaningful learning experience, increase student participation, and strengthen understanding of concepts in the topics of temperature and heat. The implication of this research is that Dual Space Inquiry E-Student Worksheet can be used as an innovative teaching material alternative to support more effective physics learning that meets the demands of digital-era education